Targeting symbiosis-related insect genes by RNAi in the pea aphid-Buchnera symbiosis. (April 2018) - Chung, Seung Ho; Jing, Xiangfeng; Luo, Yuan; Douglas, Angela E.
Abstract: The growth and reproduction of phloem sap-feeding insects requires the sustained function of intracellular bacteria localized in specialized cells known as bacteriocytes, giving the potential to target the bacterial symbiosis as a novel strategy for controlling sap-feeding insect pests. We focused on two genes in the pea aphid Acyrthosiphon pisum, amiD and ldcA1, which were acquired horizontally from bacteria and have the annotated function to degrade immunogenic bacterial peptidoglycan. We hypothesized that AmiD and LdcA1 function to eliminate peptidoglycan fragments released by the bacterial symbiont Buchnera inhabiting the bacteriocytes, thereby protecting the Buchnera from host attack. Consistent with this hypothesis, expression of amiD and ldcA1 was enriched in bacteriocytes and varied significantly with aphid age, conforming to an inverse curvilinear relationship for amiD and negative linear relationship for ldcA1. RNAi against amiD and ldcA1 administered orally to larval pea aphids caused a significant reduction in Buchnera abundance and activity, accompanied by depressed aphid growth rates. For RNAi experiments, the aphids were co-administered with dsRNA against an aphid nuclease nuc1, protecting the dsRNA against non-specific degradation. These experiments demonstrate that selective suppression of insect symbiosis-related gene function can reduce the performance of an insect pest. Phylogenetic analysis identified amiD and ldcA1 in sequenced genomes of other aphid species, and amiD in related groups of phloem-feeding insects, offering the opportunity for specific controls against a range of insect pests. Graphical abstract: Highlights: The bacterial-derived genes amiD and ldcA1 are preferentially expressed in aphid bacteriocytes. RNAi-mediated reduction of amiD and ldcA1 expression depresses the bacterial symbiosis and aphid performance. dsRNA stability and RNAi efficacy are promoted by RNAi-mediated reduction of aphid gut nuclease transcripts. amiD and ldcA1 genes are detected in the genome of multiple aphid species and, for amiD, a psyllid.